0
$\begingroup$

I've the following problem:

$$S=\frac{\partial}{\partial\alpha_1}\left\{\sum_{m=1}^k\left(\alpha_1\cdot x_m^n+\alpha_2\cdot x_m^{n-1}+\dots+\alpha_z\right)^2\right\}$$

How can I reduce this problem to a simpler form?


My work, I wrote:

$$S=\sum_{m=1}^k\left\{\frac{\partial}{\partial\alpha_1}\left(\alpha_1\cdot x_m^n+\alpha_2\cdot x_m^{n-1}+\dots+\alpha_z\right)^2\right\}$$

And now I does not know how to go further.

$\endgroup$
0
$\begingroup$

Chain rule $$\frac{\partial}{\partial x}f(x)^2=2f(x)\frac{\partial f}{\partial x}$$ $$S=\sum_{m=1}^k\left\{\frac{\partial}{\partial\alpha_1}\left(\alpha_1\cdot x_m^n+\alpha_2\cdot x_m^{n-1}+\dots+\alpha_z\right)^2\right\}$$ $$S=\sum_{m=1}^k\left\{2 x_m^n \left(\alpha_1\cdot x_m^n+\alpha_2\cdot x_m^{n-1}+\dots+\alpha_z\right)\right\}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.